Welcome from FAB 2023 Chairs - Kaya, Buket; Kaya, Mehmet; Peng, Peter (Association for Computing Machinery, Inc, 2023)
[Abstract Not Available]
15th IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining, ASONAM 2023 -- 6 November 2023 through 9 November 2023 -- Kusadasi -- 198206